Innovation for de-growth: A case study of counter-hegemonic practices from Kerala, India. (1st October 2018) - Pansera, Mario; Owen, Richard
Abstract: Our research focuses on the cross-pollination of the discourses of innovation and (post)development in the Global South. We suggest that the buzzword innovation is progressively infiltrating the lexicon and situated practices of development. Within this a hegemonic framing of innovation is emerging that leverages the language of inclusion to promote connection to, and participation in, the global free market economy. This, we hypothesise is closing down a broader debate concerning the goals and roles of innovation and technology in the so called developing world. At the same time, our research suggests that this emerging hegemony is contested, presenting as alternative, minority framings with different normative underpinnings for technology and innovation that challenge the pro-growth and market-led dominant paradigm. We present the results of one of these through a qualitative in-depth case study conducted in the Indian state of Kerala. The case provides interesting insights for the degrowth community in two regards. First it shows a concrete example of an alternative framing of technology underpinned by a set of normative principles connected to those of degrowth. Second, the case shows that alternative technological paradigms based on principles aligned with those of degrowth are not only possible, but can and do co-exist with the hegemonic paradigm. Highlights: The paper suggests that the buzzword 'innovation' is progressively infiltrating the lexicon of development. The narrative of innovation in the South tends to promote market-based development. Degrowth principles in the North are echoed by alternative, minority framings of technologies in the South. The paper presents the results of a qualitative case study of one such framing conducted in the Indian state of Kerala.